Developing Ethical Frameworks in Animal-Assisted Social Service Delivery in Aotearoa New Zealand. (23rd April 2018) - Walker, Peter; Tumilty, Emma
Abstract: Whilst social services have traditionally operated from a humanist informed practice perspective, social service interventions are increasingly including non-human animals as a key part of rehabilitation, therapy and assistance activities. While there is extensive literature documenting the human–animal bond and the benefit to social service clients of such animal-assisted interventions, there is an increasing call in the literature for the development of an ethical framework to guide such activities. At present, there are fragmented and ad-hoc ethical guidelines that consider the welfare of the service and assistance animals. This lack of an ethical code/s of conduct for practitioners working with non-human animals can lead to the possibility of harm occurring to service and assistance animals in social service activities. This paper reports on interviews with practitioners in Aotearoa New Zealand who use non-human animals to assist them in their practice to contribute to a discussion to develop a more informed framework for ethical conduct with service and assistance animals that considers the realities of practitioners situations as well as the needs of non-human animals.